2003
DOI: 10.1007/3-540-45015-7_26
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a New 3D/2D Registration Criterion for Liver Radio-Frequencies Guided by Augmented Reality

Abstract: International audienceno abstrac

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 15 publications
0
30
0
2
Order By: Relevance
“…The interested reader will find practical applications in computer vision to compute the mean rotation [32,33] or for the generalization of matching algorithms to arbitrary geometric features [65]. In medical image analysis, selected applications cover the validation of the rigid registration accuracy [4,66,67], shape statistics [7] and more recently tensor computing, either for processing and analyzing diffusion tensor images [10,8,9,11], or to model the brain variability [12]. One can even find applications in rock mechanics with the analysis of fracture geometry [68].…”
Section: Discussionmentioning
confidence: 99%
“…The interested reader will find practical applications in computer vision to compute the mean rotation [32,33] or for the generalization of matching algorithms to arbitrary geometric features [65]. In medical image analysis, selected applications cover the validation of the rigid registration accuracy [4,66,67], shape statistics [7] and more recently tensor computing, either for processing and analyzing diffusion tensor images [10,8,9,11], or to model the brain variability [12]. One can even find applications in rock mechanics with the analysis of fracture geometry [68].…”
Section: Discussionmentioning
confidence: 99%
“…More realistic but less widely applicable 'gold standard' approach is to use some independent and sufficiently accurate method to determine the true deformation, such as using special markers for validation which are not used for registration [23]- [25]. A "bronze standard" [26], [27] uses a robust mean of several registration algorithms as a reference. The registration accuracy can also be estimated indirectly, from ground truth segmentations [28], [29] or by its ability to create good generative models [30].…”
Section: Related Work On Image Registration Accuracy Evaluationmentioning
confidence: 99%
“…In this context, 3D points are spatial coordinates of fiducials reconstructed from data stemming from the scanner, and 2D points are pixel coordinates corresponding to fiducials in both camera views. The experimental study, carried out with an abdominal phantom showed that superimposition accuracy for targets located inside the model reaches an average lower than 2 mm after fiducial registration [15]. …”
Section: An Optimal Model Registrationmentioning
confidence: 98%
“…These fiducials, visible in both CT-scan and video images, are automatically extracted and matched thanks to several robust algorithms that were validated in [14]. In order to carry out this registration, we orient two tri-CDD digital color cameras jointly calibrated toward the patient with an angle above 20 for an accurate stereoscopic registration [15]. These cameras are connected to a personal computer thanks to a Matrox Meteor II acquisition card allowing the simultaneous acquisition of two video sources.…”
Section: An Optimal Model Registrationmentioning
confidence: 99%
See 1 more Smart Citation